HEROIC JOURNEY OF WADE WATTS IN ERNEST CLINE’S READY PLAYER ONE - Pratama, Zumaidil Arif; Kuncara, Singgih Daru; M., Fatimah (Fakultas Ilmu Budaya Universitas Mulawarman, 2021)
Myth and Heroes have been a part of humanity’s culture since long time ago. Campbell argues that all myth comes from a single source and dub it as the Monomyth. In these days and age, heroes still exist within the various media that we consume every day and one such work is Ernest Cline’s Ready Player One. The purpose of this study is to prove that monomyth and the characteristics of myth can be found within Ready Player One by examining its main character, Wade Watts. This study used the descriptive qualitative method to explain the story. The study employs two theories to describe Wade’s journey. First, it used the Monomyth by Joseph Campbell as the primary theory to analyze the hero’s journey from the beginning till the end. Second, Northrop Frye’s Theory of Myth is used to analyze the characteristic of myth and determine the work’s genre of myth. The result of the study showed that the monomyth is applicable in this work, all stages of monomyth can be found within the work, except for the refusal to the call. Furthermore, by employing Frye’s theory, the research showed that the most common characteristics of myth that appears in this research belongs to the Summer: Romance. These two analyses were able to successfully describe Wade’s journey and myth.